Effects of exogenous melatonin on expressional differences of immune-related genes in cashmere goats - Chai, Yuan; Liu, Zaixia; Fu, Shaoyin; Liu, Bin; Guo, Lili; Dai, Lingli; Sun, Yanyong; Zhang, Wenguang; Li, Chun; Liu, Taodi (Frontiers in Genetics, 2022)
The interplay between melatonin and immune system is well recognized in humans, the true integration of research on cashmere goat is still far from clear, especially for cashmere goat maintained in wool and cashmere growth. Our research applied a variety of approaches to identify the available evidence that the complex regulated network between the immune-related genes and TFs and explored the effects of melatonin on their expression. In total, 1599 immune related genes and 1756 immune related genes were found in the blood and the skin of cashmere goats, respectively and 24 differentially expressed immune-related GO terms were highly expressed in blood after melatonin implantation. Moreover we found that melatonin-dependent networks between the TFs and immune-related genes in cashmere goat. The 3 major regulatory networks are interconnected through TFs and the TFs are also expressed in blood and skin tissue of cashmere goat, such as PHF5A、REXO4、STRAP、JUNB、GATAD2A、ZNF710、VDR. In addition, most genes in the network are involved in WNT pathway, which is related to wool and cashmere growth regulation, such as VDR、JUNB, TRIB3. On the network basis, we developed a knockout mouse model to identify the network interaction, we found that 8 high sulfur protein genes, 12 KRT genes and 19 KRTAP genes were almost not expressed in the skin of TRIB3-/- rat, the expression of these genes was related to the growth of wool and cashmere. The network analysis revealed that melatonin may activate the immune-related genes interact network to affect the expression of wool and cashmere growth related Genes. In conclusion, we sketch some particularly promising avenues for future investigation into the far too long ignored the cashmere goat of immune-related genes and melatonin in the wool and cashmere growth.